PROFIL TINGKAT KESEHATAN KEUANGAN PERUSAHAAN PEMBIAYAAN BERDASARKAN SURAT EDARAN OJK NOMOR 1/SEOJK.05/2016 TENTANG TINGKAT KESEHATAN KEUANGAN PERUSAHAAN PEMBIAYAAN - Yopi Ivanda; Yvonne Augustine; Fanny Rachamdhitya (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2016)
This research was took 12 samples of financing companies in Indonesia to see how the profile of capital, quality of financing receivables, profitability and liquidity to the financial soundness of respective companies. Through the financial statements of the financing companies than processed according to the rules from OJK to see the profile of each of these factors on the level of financial soundness. Based on the financial statements of all 12 financing companies which are explicitly who suffered losses and there is a very minimum level of liquidity show an initial signal that there are some financing companies that the financial condition is less sound.